Development and Psychometric Properties of the Sussex-Oxford Compassion Scales (SOCS). (January 2020) - Gu, Jenny; Baer, Ruth; Cavanagh, Kate; Kuyken, Willem; Strauss, Clara
Compassion has received increasing societal and scientific interest in recent years. The science of compassion requires a tool that can offer valid and reliable measurement of the construct to allow examination of its causes, correlates, and consequences. The current studies developed and examined the psychometric properties of new self-report measures of compassion for others and for the self, the 20-item Sussex-Oxford Compassion for Others Scale (SOCS-O) and 20-item Sussex-Oxford Compassion for the Self Scale (SOCS-S). These were based on the theoretically and empirically supported definition of compassion as comprising five dimensions: (a) recognizing suffering, (b) understanding the universality of suffering, (c) feeling for the person suffering, (d) tolerating uncomfortable feelings, and (e) motivation to act/acting to alleviate suffering. Findings support the five-factor structure for both the SOCS-O and SOCS-S. Scores on both scales showed adequate internal consistency, interpretability, floor/ceiling effects, and convergent and discriminant validity.